Examining the Roles of Traditional Rulers in Peace Building in Northeast Nigeria - Emmanuel, Joseph (Darul Yasin Al Sys, 2025)
This study examines the role of traditional rulers in peacebuilding efforts in Northeast Nigeria, focusing on the states of Borno, Adamawa, Yobe, and Gombe using a qualitative case study approach. The case study design allows for an in-depth exploration of real-life interactions, contextual factors, and lived experiences within conflict-affected communities. The study's population includes representatives from local and international NGOs, traditional rulers (e.g., emirs, district heads, village chiefs), and community leaders involved in peace and reconciliation processes. A purposive sampling technique was used to select participants with relevant expertise and experience in peacebuilding efforts. Data were collected through semi-structured interviews, focus group discussions (FGDs), and key informant interviews (KIIs), providing rich qualitative insights into the roles and contributions of key stakeholders. Thematic analysis was employed to analyze the data, identifying recurrent themes and patterns related to peacebuilding and collaboration. The findings reveal the critical role of traditional rulers in conflict mediation and the positive impact of NGO-traditional ruler partnerships. Challenges such as resource limitations, security concerns, and the erosion of authority among younger generations were identified. The study highlights the importance of strengthening these collaborations to enhance peacebuilding outcomes in the region.